2018
DOI: 10.1039/c8cp00091c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the features on the OH + SO2potential energy surface using theory and testing its accuracy by comparison to experimental data

Abstract: Ab initio theory has been used to identify the pre-reaction complex in the atmospherically important reaction between OH + SO2, (R1), where the binding energy of the pre-reaction complex was determined to be 7.2 kJ mol-1. Using reaction rate theory, implemented with the master equation package MESMER, the effects of this complex on the kinetics of R1 at temperatures above 250 K have been investigated. From simulations and fitting to the experimental kinetic data, it is clear that the influence of this pre-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…Similar results were reported and discussed by Golden for the OH + C 2 H 4 reaction, and more recently by Medeiros et al. for the OH + SO 2 reaction which, like reaction 1a, involves the formation of a weakly bound (1.7 kcal mol –1 ) prereaction complex that proceeds over a submerged barrier to HOSO 2 product …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar results were reported and discussed by Golden for the OH + C 2 H 4 reaction, and more recently by Medeiros et al. for the OH + SO 2 reaction which, like reaction 1a, involves the formation of a weakly bound (1.7 kcal mol –1 ) prereaction complex that proceeds over a submerged barrier to HOSO 2 product …”
Section: Resultssupporting
confidence: 89%
“…18 Extracting kinetics from a PES involving a prereaction complex is of significant interest as the local energy minima can cause strongly non-Arrhenius behavior and influence the collision-induced energy transfer process. [34][35][36][37] In the case of reaction 1a, the magnitude of the vdW complex well preceding reaction is comparable to both the computed submerged barrier height (0.1-2.24 kcal mol -1 ), 14,23 and the expected accuracy of high-level calculations (± 1-2 kcal mol -1 ). Consequently, theoretical studies of the OH + C 2 H 4 reaction have reported barrier heights both above 18,19 and below the entrance channel, [13][14][15][16]20,23 depending on the level of theory employed.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations